2008
DOI: 10.1111/j.1399-3038.2007.00670.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral desensitization in children with immunoglobulin E‐mediated cow’s milk allergy – follow‐up at 4 yr and 8 months

Abstract: Until now, the basic treatment for food allergy has been to avoid the offending item. This approach is difficult in the case of common foods and in the case where there is a risk of severe reaction after consuming the offending food, even inadvertently. This is the follow-up of a previous study aimed at desensitizing 21 children with immunoglobulin E (IgE)-mediated cow's milk (CM) allergy. This protocol was totally or partially successful in 85% of cases, but failed in the remaining 15%. Our aims were to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0
10

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 18 publications
6
64
0
10
Order By: Relevance
“…In 2004, Meglio et al [36] performed a pilot study of 21 children treated with 6 months of OIT that resulted in a 72% success rate of tolerating a target dose of 200 mL of cow's milk daily, with an additional 14% of patients achieving partial desensitization. Of note, after a 4-year follow up, 70% at least partially tolerated milk, with significant reductions in serum-specific cow's milk IgE and skin prick test results [37]. A number of other nonrandomized milk OIT studies also demonstrated overall success in achieving desensitization [38][39][40].…”
Section: Milk Oitmentioning
confidence: 99%
“…In 2004, Meglio et al [36] performed a pilot study of 21 children treated with 6 months of OIT that resulted in a 72% success rate of tolerating a target dose of 200 mL of cow's milk daily, with an additional 14% of patients achieving partial desensitization. Of note, after a 4-year follow up, 70% at least partially tolerated milk, with significant reductions in serum-specific cow's milk IgE and skin prick test results [37]. A number of other nonrandomized milk OIT studies also demonstrated overall success in achieving desensitization [38][39][40].…”
Section: Milk Oitmentioning
confidence: 99%
“…La posibilidad de que la edad de ablactación y la introducción de alimentos nuevos en los infantes como cofactores de enfermedades alérgicas se encuentran en discusión (24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). En nuestros estudios de 1994, no encontramos mayores ventajas de una prolongada lactación materna para la prevención de enfermedad alérgica en el Ecuador, existiendo más bien una correlación positiva entre la introducción precoz de leche bovina procesada y alergia (35 , 36).…”
Section: Discusión Y Conclusionesunclassified
“…Die Wirksamkeit dieser Methode wurde zwar mehrfach bei Patienten mit Kuhmilch-und Hühnerei-allergie gezeigt [43,44], aber der Effekt scheint leider nicht anhaltend zu sein. Dieses Verfahren wird insbesondere dort angewandt, wo Nahrungsmittel, wie z.…”
Section: Spezifische Orale Toleranzinduktionunclassified